To study the clinicobacteriological profile and antibiotic susceptibility pattern of community acquired pyodermas - Gugani, Harshita; Malhotra, Sita; Malhotra, S.K.; Kaur, Shailpreet (International Journal of Medical Research and Review, 2016)
Background: Pyodermas are the pyogenic skin infection encountered in dermatologic clinic and is mainly caused by Staphylococci and Streptococci. Aim: To find out causative organisms in community acquired pyodermas and their current antibiotic susceptibility patterns. Materials and Methods: All the patients attending the Dermatology OPD in Government Medical College, Amritsar were screened over 18 months and swabs were sent for culture and sensitivity. Results: The maximum incidence of pyodermas was observed in patients of 21-40 years i.e 82(51.24%). Most of the patients were males i.e 95(64%) than females i.e 64(40%). Out of 160 patients, maximum patients i.e. 109(68.13%) had secondary pyoderma and 51 (31.87%) had primary pyodermas. Out of 160 samples, growth was obtained in 148 (92.50%) samples while 12(07.50%) samples showed no growth. Most common organisms isolated was Staphylococcus aureus in 70 (43.75%) cases followed by CONS in 20(12.50%) cases. Among the Gram negative organisms E.coli was observed to be the common isolate in 16(10.00%) cases followed by Pseudomonas aeruginosa in 12(07.50%) cases. On antibiotic susceptibility testing, Gram positive organisms, maximum sensitivity i.e 100% was seen to vancomycin, linezolid and maximum resistance i.e 84.29% was seen to ampicillin. Among the Gram negative isolates maximum sensitivity i.e 100% was seen to Imipenem, Piperacillin -Tazobactum and Sulbactam-Ceftazidime and maximum resistance i.e 100% was seen to ceftazidime in case of Acinetobacter. Conclusion: This study gives an indication of the present pattern of bacteriological profile and antibiotic susceptibility pattern of pyodermas in a tertiary care hospital in north India.